Comparison of bacterial cellulose produced from nata-de-coco and kombucha - Wang, Ke; Ma, Qian; Zhao, Ju-Mei; Cao, Miao; Wang, Shu-Dong (Wydawnictwo Politechniki Łódzkiej, 2022)
In the current study, two different bacterial cellulose including nata-de-coco bacterial cellulose (NBC) and kombucha bacterial cellulose (KBC) were compared. The morphological features, functional groups and crystals were carried out by scanning electron microscopy (SEM), attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) and X-ray diffraction (XRD). Thermogravimetric analysis was used to investigate the stability. Mechanical property and water content were evaluated by tensile strength tester and gravimetric method. Results revealed slightly loose fibril arrangement in KBC compared to NBC. The crystallinity, thermal and mechanical properties of KBC were lower than those of NBC. Water content of KBC was slightly higher than that of NBC.
Keywords: nata-de-coco bacterial cellulose (NBC); kombucha bacterial cellulose (KBC); structure; crystallinity; thermal stability; mechanical property; celuloza bakteryjna Nata-de-coco; celuloza bakteryjna kombucha; struktura; stabilność termiczna; właściwości mechaniczne